Lifestyle-Related Diseases and Metabolic Syndrome - Shiomi, Naofumi (IntechOpen, 2022)
Lifestyle-related diseases are caused by an unbalanced diet and irregular, undesirable lifestyle, leading to a condition called metabolic syndrome. Rather like dominoes falling, these diseases develop one after another. Owing to changes in dietary habits and working environments, the incidence of lifestyle-related diseases, obesity, and metabolic syndrome is increasing globally, resulting in a serious social problem that needs to be solved. This book deals with recent studies on lifestyle-related diseases and metabolic syndrome, and the following three topics are discussed: (1) characteristics of metabolic syndrome and lifestyle-related diseases; (2) the relationship between metabolic syndrome and several diseases; and (3) effective interventions to prevent lifestyle-related diseases. This book provides new ideas for the treatment and prevention of metabolic syndrome and lifestyle-related diseases.